Medication errors in the adult emergency unit of a tertiary care teaching hospital in Addis Ababa - Gediwon Negash; Yonathan Kebede; Segewkal Hawaze (Archives of Global Professionals, 2013)
Background: The emergency unit is a high risk environment for inappropriate medication use due to stressors and time sensitive nature of the service. Objective: To assess incidence and type of Medication Errors in Tikur Anbesa Specialized Hospital. Materials and Methods: A prospective cross-sectional study was conducted on the interventions by prescribing physicians and attending nurses for patients seen at the emergency unit of Tikur Anbesa Specialized Hospital from May 2-20, 2011. Data about interventions were collected from the medication charts. Medication errors were identified by comparing prescriptions and administration records with standard treatment algorithms. Descriptive statistics was used to meet the objective of the study. Results: A total of 742 patient charts were reviewed which contained 1058 prescriptions containing 2968 orders. Medication errors were found to be 22781 (54.84%) with rate of 30.70 errors per patient and 1627.21 errors per day. Prescription errors, administration errors from recorded ones, absence of administration record were 7314 (32.11%), 991 (4.35%), and 14476 (63.54%) respectively. Conclusion: Incidence and types of medication errors committed in Tikur Anbesa Specialized Hospital Adult Emergency Unit were substantiated; moreover, necessary information on factors within the healthcare delivery system that predispose healthcare professionals to commit errors have been pointed, which should be addressed by healthcare professionals through multidisciplinary efforts and involvement of decision makers at national level.